Enhancing steel slag cement mortar performance under low-temperature curing through alkali activation: mechanisms and implications - Ye, Wei; Feng, Tengteng; Sun, Wangwen; Gómez-Zamorano, Lauren Y. (Frontiers in Materials, 2025)
The effective utilization of steel slag waste offers a sustainable approach to advancing construction materials, particularly in cold regions. This study investigates the influence of alkaline activators and low-temperature curing (10°C) on the performance of steel slag cement mortar. The setting time of mixed slurry with varying steel slag powder content was analyzed, along with the effects of different activators and water glass modulus on compressive strength. Advanced characterization techniques, including thermogravimetric analysis (TGA), X-ray diffraction (XRD), and scanning electron microscopy (SEM), were employed to examine the hydration products and microstructural evolution of optimally activated samples. The results indicate that a Na2O content of 4% significantly enhances the compressive strength of steel slag cement mortar. The composite activator (containing water glass and NaOH) exhibited superior performance compared to neat NaOH, increasing the strength. Activated samples demonstrated increased early hydration products, as evidenced by intensified Ca(OH)2 diffraction peaks. The activators facilitated calcium ion dissolution, reduced the activation energy of cementitious materials, and accelerated hydration kinetics, leading to the enhanced formation of hydration products. Microstructural analysis revealed that the activators disrupted the vitreous network structure of the steel slag powder, promoting more complete hydration and the formation of dense C-S-H gels and Ca(OH)2. This densification reduced porosity and significantly improved the mechanical properties of the cement matrix. These findings highlight the potential of alkaline-activated steel slag cement mortar as a sustainable and high-performance material for construction applications in cold climates.